Kurisumala: Francis Mahieu Acharya-A Pioneer of Christian Monasticism in India. - Marthe Mahieu-De Praetere. Susan Van Winkle Tr. Edward T. Ulrich Rev
Kurisumala: Francis Mahieu Acharya-A Pioneer of Christian Monasticism in India. Marthe Mahieu-De Praetere. Trans. by Susan Van Winkle. Kalamazoo, Mich.: Cistercian Publications, 2007, xv + 394 pp